The Regression of Students' Reading Habits, Intrapersonal Intelligence, and the Level of Reading Comprehension - Rina Musliha; Muhammad Hasbi; Muhammad Tahir; Amirullah Abduh (International Journal of Language, Education, and Literature, 2025)
The purpose of this study was determined the correlation among students' reading habits, intrapersonal intelligence, and reading comprehension levels. There was two different types of instruments, namely questionnaires and reading comprehension tests where students' score results identified the correlation between students' reading habits, intrapersonal intelligence, and their reading comprehension levels that focused on inferential level. Quantitative research with a correlation design in this study. The sample of this study was showed to 30 students of the 12th - grade Language Class at Man 1 Bone from the language department who had English language skills was powerfull where the influence of reading habits and intrapersonal intelligence was related to their reading comprehension levels. All of the data in this study measured with SPSS 29 version for windows. In this study, researcher used Pearson Correlation Product Moment to determine the value of both variables. Researcher found that the R value of the correlation between students' reading habits and reading comprehension levels was 0.369 and a significance of 0.045, which means that the variables are interrelated with a moderate correlation level. In addition, the R value of the correlation between intrapersonal intelligence and reading comprehension level is 0.374 and the significance is 0.042, which means that the variables are interrelated with a moderate level of correlation. Then, researcher used Multiple Linear Regression to determine the correlation among students' reading habits, intrapersonal intelligence and reading comprehension levels. The results of the regression analysis of the R value are 0.555 and significance 0.007 which means that the variables are interrelated with a moderate and significant correlation level. Students' reading habits and intrapersonal intelligence are positively correlated with reading comprehension levels, meaning that the more students was accustomed to reading followed by intrapersonal intelligence, the more they are able to concieve the contents of reading.